STRATEGI PENGGUNAAN INSTAGRAM â€œDEWAHOYA COFFEE AND MILKâ€ SEBAGAI MEDIA KOMUNIKASI PEMASARAN TEMPAT NONGKRONG ASIK DI KOTA WATES KABUPATEN KULON PROGO - Kartika, Widyaningtyas Virgo (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACT New media is currently used as an alternative to approach consumers and potential customers. Promotional activities are not only carried out conventionally, but maximize the existence of this new media. Digital Marketing is a marketing activity that uses the internet and information technology to expand and enhance the functions of traditional marketing. Social media with all its advantages and disadvantages give a big role in the marketing communication process. This study discusses the strategy of using Instagram as a marketing communication medium carried out by